Loss of superfluidity in a Bose-Einstein condensate via forced resonant oscillations - Adhikari, S. K. (Elsevier B.V., 2003)
We predict the loss of superfluidity in a Bose-Einstein condensate in an axially symmetric harmonic trap alone during resonant collective oscillations via a classical dynamical transition. The forced resonant oscillation can be initiated by (a) periodic modulation of the atomic scattering length with a frequency that equals twice the radial trapping frequency or multiples thereof, or by (b) periodic modulation of the radial trapping potential with a frequency that equals the radial trapping frequency or multiples thereof. Suggestion for future experiment is made. (C) 2003 Elsevier B.V. B.V. All rights reserved.
Keywords: Bose-Einstein condensation; superfluid-insulator transition